Double-sided moral hazard, information screening and the optimal contract. Issue 4 (21st November 2016) - Xue, Jin; Fei, Yiwen
Abstract : Purpose: In the practice of venture capital investment, the venture capital will not only claim the share of the enterprise's future output, but also a certain amount of fixed income. The purpose of this paper is to examine the optimal contract which blends the variable ownership income and the fixed income theoretically so as to provide a keen insight into the venture capital practice. Design/methodology/approach: This paper establishes an extended principal-agent model and researches on the design of optimal contract dominated by venture capital with double-sided moral hazard and information screening. Findings: By establishing theoretical models, the main findings are: first, high-quality enterprise tends to relinquish less ownership but give more fixed return to the venture capital as compensation in order to obtain the venture capital financing; second, low-quality enterprise is willing to relinquish more ownership but give less fixed return to the venture capital for financing; third, due to the existence of double-sided moral hazard, neither of the venture capital and the enterprise will exert their best effort. Originality/value: This paper furthers the application of principal-agent model in the field of venture capital investment and researches on the optimal contract, considering double-sided moral hazard and adverse selection at the same time originally.